Improvement of Physical and Mechanical properties of High-performance Sand Concrete with different Silica Fume content - Kaci Chalah; Aghiles Hammas; Abdelbaki Benmounah (Advances in Civil and Architectural Engineering)
Silica fume (SF) is widely used for the improvement of several properties of cementitious materials. For this purpose, this study investigated the effect of SF content on the mechanical and durability properties of high-performance sand concrete (HPSC). The experiment work consists of the preparation of HPSC by adding different amounts of SF (0 %, 4 %, 6 %, and 8 %) as a replacement for ordinary Portland cement at a constant water-to-cement ratio of 0,35. The compressive and flexural strengths were performed on the HPSC samples with two standardised sizes of 40 mm × 40 mm × 40 mm and 40 × 40 × 160 mm, which cured during 3, 7, and 28 d. In contrast, both water absorption and water capillary absorption analyses were conducted under a prismatic size of 40 × 40 × 160 mm and cured for 28 d. Based on the test results, the optimal amount of SF was obtained using mechanical strength analysis (6 %). The results showed that at this content of SF, the compressive strength and flexural strength increased by 6,19 and 10,03 %, respectively. In contrast, the addition of SF above this concentration slightly increased the mechanical properties. However, the lowest value of water absorption was obtained for the sample with 6 % SF content. Indeed, at this concentration of SF, the water absorption and the capillarity values of HPSC samples decreased by 8,80 and 8,57 %, respectively.